Integrative Spiritual-Economic Model in Community Empowerment Based on Micro Waqf Bank at Fajar Pelita Harapan Islamic Boarding School - Mohd Winario; Zubaidah Assyifa; Rahmawati Rahmawati; Merry Meilany; Nilam Erman; Henry Martin Adriansyah (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: Islamic boarding schools are traditional Islamic educational institutions that have an important role in the educational, social and economic development of society in Indonesia. This study aims to analyze the sharia-based community economic empowerment model through the Fataha Micro Waqf Bank (BWM) at the Fajar Pelita Harapan Islamic Boarding School in Maredan Village, Tualang District. Methods: The study used a qualitative descriptive approach involving 30 informants consisting of Islamic boarding school administrators, BWM Fataha managers, and the surrounding community as financing program customers. Data were obtained through in-depth interviews, observation, and documentation through the stages of data reduction, data presentation, and conclusion drawing. Results: The results show that the implemented empowerment model is integrative by combining Islamic microfinance, spiritual guidance, business mentoring, and group strengthening through the kumpi system. This program is able to increase access to business capital, strengthen community economic independence, improve Islamic financial literacy, and empower women as micro-entrepreneurs. In addition, the Islamic boarding school plays a role as a center for social capital and community moral development. However, the program still faces obstacles such as low entrepreneurial literacy, limited business innovation, and limited mentoring resources. This research shows that Islamic boarding schools have strategic potential as centers for sustainable sharia-based community economic empowerment Conclusion and suggestion: This study shows that the sharia-based community economic empowerment model implemented by the Fataha Micro Waqf Bank (BWM) in the Fajar Pelita Harapan Islamic Boarding School environment uses an integrative approach that combines sharia microfinance, spiritual guidance, business mentoring, and strengthening group solidarity through the kumpi system.